Risk Assessment of Manufacturing Hydraulic Press Paving Block Machine - Rahmatullah; Bobby Umroh; Arfis Amiruddin; Yudi Daeng Polewangi; Sudirman Lubis; Edi Sarman Hasibuan; Irpansyah Siregar; Faisal Lubis, (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
Hazard is the intrinsic property of a substance, equipment or physical situation with potential to cause harm. Hazards can pose risks, and risks must be assessed. Assessing risk can be done by imagining the impact that will arise to determine the level of risk. Knowing the level of risk can make risk control more controlled and comprehensive. This paper describes the improvement of the risk assessment method in the manufacturing industry using the HAZOP. HAZOP approach applied to identify and control potential hazards, risks in the workplace. The HAZOP approach was chosen because HAZOP is a qualitative method that is easy to learn, thorough, systematic, logical, and demands to obtain accurate results. In the process of making paving block machines there are several processes carried out starting from the beginning of cutting the material to the completion of the machine and testing its operation. In this process, risk assessment procedures and identification of potential hazards must be carried out to plan to minimize or control them. It is proposed to control the problems and negative impacts on the paving block machine fabrication process by applying the HAZOP method.